Performance and design optimisation of an apparatus for distilling palm wine(Elaeis guineensis) by controlling thermal operations - AHOUANNOU, CLÉMENT; TCHOBO, PAUL FIDÈLE; SANYA, EMILE ADJIBADÉ; LOKOSSOU, Christa; Soumanou, M. Mohamed (My University, 2015)
Mastery of thermal control in the craft distillation processing operations of fermented wine from Elaeis guineensis is needed to improve and enhance the resulting Beninese alcoholic drink, sodabi. In this study, craft distillation of palm-wines from three municipalities of southern Benin was investigated and the influences of wine vapour temperature on some physical-chemical parameters of the liquor produced were analysed. Palm wines, handcraft distilled, presented relative density values between 0.90 to 0.96, volumetric alcoholic strength from 35.16 to 46.29% (v/v), acetic acid content of 1.17 to 3.29 g/l and pH-values of 3.7– 4.2. A series of palm-wine distillations, from liquor-producing farms, controlled by maintaining the heating temperature at 94 ± 1 °C, was also performed. The values of characteristic parameters were then respectively 0.84 to 0.93, 38.05 to 52.72% (v/v), 0.35 to 0.39 g/l and 4 to 4.25. From analysis of these results, we conclude that the high values of wine heating temperature, well above 100 °C, induce a significant increase in relative density and acetic acid content of sodabi and a decrease of its volumetric alcoholic strength and pH-value. Controlled laboratory distillation yielded a distillate which has the best features of spirituous and thermal efficiency.
Keywords: Palm-wine; heating; sodabi; characteristics; quality